TCS Language & Literacy English Resource Pack Term 1 KG - The City School (Pakistan) (Lahore The City School)
This resource pack is designed for KG students to enhance their literacy and language skills. The book covers reading, writing, and oral language exercises suitable for early years learners.
This book is part of the Language and Literacy series for KG students. It includes teacher-guided exercises for language development.
Keywords: Language arts (Kindergarten)- Literacy (Early childhood)